2008
DOI: 10.1249/mss.0b013e31815b0dcb
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Electromyographic Mapping during Delayed-Onset Muscle Soreness

Abstract: Novel topographical mapping of both surface EMG and PPT of the quadriceps showed site-dependent effects of eccentric exercise, probably attributable to variations in the morphological and architectural characteristics of the muscle fibers. Greater manifestations of DOMS in the distal region of the quadriceps may indicate a greater susceptibility of this region to further injury after eccentric exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 39 publications
13
57
0
Order By: Relevance
“…23,24 For example, Edwards et al 23 reported that, after 15 minutes of eccentric stepping exercise, muscle pain in the quadriceps femoris was located close to the distal insertion of the myotendinous junction of the vastus medialis and lateralis. Hedayatpour et al 25 observed a greater reduction in PPT in the distal quadriceps region than in the proximal region after 100 eccentric knee extensions. In contrast, Andersen et al 26 found that tibialis anterior muscle belly sites became more sensitive to pressure stimulation than muscle-tendon junction sites after eccentric exercise.…”
mentioning
confidence: 97%
“…23,24 For example, Edwards et al 23 reported that, after 15 minutes of eccentric stepping exercise, muscle pain in the quadriceps femoris was located close to the distal insertion of the myotendinous junction of the vastus medialis and lateralis. Hedayatpour et al 25 observed a greater reduction in PPT in the distal quadriceps region than in the proximal region after 100 eccentric knee extensions. In contrast, Andersen et al 26 found that tibialis anterior muscle belly sites became more sensitive to pressure stimulation than muscle-tendon junction sites after eccentric exercise.…”
mentioning
confidence: 97%
“…EMG and vastus lateralis respectively) and anterior superior iliac spine (Hedayatpour, Falla, et al, 2008). Before electrode placement, the skin was shaved and lightly abraded at the selected locations.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted in accordance with the Declaration of Helsinki, approved by the local Ethics Committee (BOJ 13950701), and written informed consent was obtained from all subjects prior to inclusion. The number of participants was based on previous studies examining the effects of exercise on neuromuscular activity of same muscle (vastus medialis, rectus femoris, vastus lateralis), which showed that 10 subjects were sufficient to show a difference Hedayatpour, Falla, Arendt-Nielsen, & Farina, 2008).…”
Section: Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodes were placed over the quadriceps components at 10% of the distance between medial border, superior border and lateral border of the patella (for vastus medialis (VM), rectus femoris (RF) and vastus lateralis (VL) respectively) and anterior superior iliac spine 24 . Before electrode placement, the skin was shaved and lightly abraded at the selected locations.…”
Section: Surface Emg Recordingsmentioning
confidence: 99%